Clinical consequences of circulating CD28‐negative T cells for solid organ transplantation. (8th September 2015) - Betjes, Michiel G. H.
Summary: CD28 is an important costimulatory molecule expressed on T cells, interacting with CD80 and CD86 on antigen‐presenting cells. All naïve T cells express CD28, but memory T cells may become CD28 negative (CD28neg) as a result of repetitive cell divisions, the influence of TNF‐alpha, and infection with cytomegalovirus. This results in accumulation of CD28neg T cells, which may constitute >50% of the total circulating T‐cell population in the elderly. The frequency of CD28neg T cells is associated with diseases such as cancer, autoimmunity, and atherosclerosis in which they may act as either effector or suppressor cells. This functional heterogeneity probably underlies the finding that the CD8posCD28neg T‐cell population harbors effector cells mediating acute allograft rejection, but also suppressor cells. The CD4posCD28neg T cells are predominantly considered to be a nonclassical risk factor for atherosclerotic disease, and their contribution to alloreactivity is less clear. CD28neg T cells depend on IL‐15 for their proliferation, and they have increased the expression of specific costimulatory molecules, such as NK receptors, TNF‐alpha receptor family members, and the adhesion/costimulatory molecule CD2. Targeting these costimulatory pathways presents potential therapeutic options to block allograft rejection mediated by CD28neg T cells which are resistant to belatacept.